'I can't tell my child they are dying'. Helping parents have conversations with their child. Issue 4 (13th March 2017) - Aldridge, J; Shimmon, K; Miller, M; Fraser, L K; Wright, B
Abstract : This paper explores the challenges of resolving conflicting feelings around talking with a child about their terminal prognosis. When children are left out of such conversations it is usually done with good intent, with a parent wishing to protect their child from anxiety or loss of hope. There is however growing evidence that sensitive, timely, age appropriate information from those with whom children have a good relationship is helpful both for the child and their family. There is no evidence that involving children in sensitive and timely discussions creates significant problems, rather that withholding information may lead to confusion, frustration, distress and anger. The authors discuss ways in which families can be supported to have these significant conversations with their children.